Polyurethane porous material as well as preparation method and application thereof
By using the water system preparation method in the preparation of polyurethane hemostatic materials, amphiphilic copolymers are generated and freeze-dried, the biocompatibility and degradability problems during foaming are solved, and the preparation of high-performance and environmentally friendly polyurethane porous materials is achieved.
Patent Information
- Application Number
- CN202510206462.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
In the preparation process of existing polyurethane hemostatic materials, biocompatibility and degradability problems caused by the foaming process, and the use of emulsifiers may affect the biocompatibility and degradation performance of the product, and there is a risk of environmental pollution.
A method of preparing biodegradable polyurethane porous materials using an aqueous system is used to produce amphiphilic copolymers by reactions of polyethylene glycol, aliphatic cyclic ester monomers and stannous octanoate, and freeze-dried under vacuum, avoiding defects in foaming and the use of emulsifiers.
The preparation of polyurethane porous materials without foaming agents and emulsifiers is realized, and biocompatibility and degradability problems are avoided. The material has excellent hemostatic effect, good mechanical properties and biocompatibility, and the process is simple and green and environmentally friendly.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, and in particular to a polyurethane porous material and a preparation method and application thereof. Background Art
[0002] Traditional hemostatic materials such as gauze and cotton balls have limited hemostatic effects, and long-term use may cause foreign body reactions and residue problems. In recent years, synthetic polymer materials have been widely used in the field of hemostatic materials due to their excellent performance.
[0003] Biodegradable polyurethane hemostatic sponge is a new type of hemostatic material that combines the excellent properties of polyurethane and biodegradability. It has good hemostatic effect and degradation performance and has attracted much attention. However, the preparation process of existing polyurethane hemostatic sponge requires foaming reaction. Although this process can give the material a porous structure and enhance its liquid absorption capacity, it also brings many problems. The reaction temperature and time need to be strictly controlled during the foaming process to ensure the uniformity and stability of the foam. The heat and gas generated during the reaction may cause defects or uneven bubbles inside the foam. In this regard, in order to ensure that the foam is uniform and fine, it is generally necessary to select a suitable emulsifier to reduce the interfacial tension between the oil and water phases and improve the uniformity and stability of the foam. However, although this method can prepare materials with good water absorption and hemostatic properties, improper selection of emulsifiers may affect the biocompatibility and degradation performance of the product. In addition, the presence of emulsifiers may also cause environmental pollution problems. Summary of the invention
[0004] In order to solve the biocompatibility and degradation problems caused by the foaming process of existing polyurethane hemostatic materials, the present invention proposes a polyurethane porous material and a preparation method and application thereof.
[0005] The technical solution of the present invention is as follows: A method for preparing a polyurethane porous material comprises the following steps: S1. Under nitrogen protection, a toluene solution of polyethylene glycol, aliphatic cyclic ester monomer and stannous octoate is heated to 120°C to 140°C for reaction for 8h to 12h. After the reaction, the solution is dissolved in dichloromethane and then precipitated with ether to obtain an amphiphilic copolymer including polyethylene glycol segments and aliphatic polyester segments. S2, then heating the amphiphilic copolymer to 100° C. to 140° C., performing vacuum dehydration for 2 h, cooling to 80° C. after dehydration, then adding diisocyanate, reacting at 80° C. to 90° C. for 2 h to 3 h to generate a prepolymer; S3, dispersing the prepolymer in water, heating to 40°C to 50°C, stirring at high speed to form a stable prepolymer emulsion, adding a chain extender to the emulsion to carry out a chain extension reaction for 3h to 4h to obtain a polyurethane emulsion; S4. Dilute the prepared polyurethane emulsion to a solid content of 5% to 10%, pour it into a mold for pre-freezing, and then freeze-dry it under vacuum conditions to obtain a polyurethane porous material.
[0006] Preferably, the aliphatic polyester in step S1 is a polymer obtained by ring-opening polymerization of an aliphatic cyclic ester monomer; the aliphatic cyclic ester monomer is at least one selected from lactide (LA), glycolide (GA), cyclopentadienone (PDO), and caprolactone (CL).
[0007] Preferably, the molecular weight of the polyethylene glycol in step S1 is 500-5000; the mass ratio of the polyethylene glycol to the aliphatic cyclic ester monomer is 1:(0.1-2.5); the mass of the stannous octoate is 0.1‰-1‰ of the sum of the masses of the polyethylene glycol and the aliphatic cyclic ester monomer.
[0008] Preferably, the diisocyanate in step S2 is any one of hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), 1,4-diisocyanate butane (BDI), and 4,4'-dicyclohexylmethane diisocyanate (HMDI).
[0009] Preferably, the molar ratio of the amphiphilic copolymer to the diisocyanate in step S2 is 1:(2.0-3.0).
[0010] Preferably, the chain extender in step S3 is a small molecule diol.
[0011] Preferably, the chain extender is any one of 1,4-butanediol, hydroquinone dihydroxyethyl ether, and ethylene glycol.
[0012] Preferably, the molar ratio of the prepolymer to the small molecule diol in step S3 is 1:(1.0-2.0).
[0013] The invention also provides a polyurethane porous material, which is prepared by applying the above preparation method.
[0014] The present invention also provides an application of the polyurethane porous material, which is applied to the field of medical materials as a hemostatic material, a tissue engineering scaffold or a drug sustained-release carrier.
[0015] Compared with the prior art, the specific beneficial effects of the present invention are: The present invention utilizes the characteristic that the reaction rate of isocyanate group (-NCO) and hydroxyl group (-OH) in the polyurethane synthesis reaction is much higher than the reaction rate with water, and innovatively proposes a method for preparing biodegradable polyurethane porous materials in an aqueous system. No foaming agent and emulsifier are required, and no foaming process is involved, thereby avoiding the biocompatibility and degradability problems caused by the foaming process. The obtained material not only has excellent hemostatic effect, but also has good mechanical properties and biocompatibility. The method is simple in process, green and environmentally friendly, and the prepared material has broad application prospects in the medical field.
[0016] The material provided by the present invention is not only applicable to hemostatic materials, but also can be used for tissue engineering scaffolds and drug sustained-release carriers, has a wide range of application potentials, and meets the requirements of modern medicine for environmental protection and sustainable development. DETAILED DESCRIPTION
[0017] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as limiting the present invention.
[0018] Example 1. Under nitrogen protection, 10.0 g of PEG with a molecular weight of 1000, 3.0 g of LA, and 2.5 mL of a 0.1 wt% stannous octoate toluene solution were heated to 140° C. for 12 h. After the reaction was completed, the amphiphilic copolymer PEG-PLA was obtained by dissolving in dichloromethane and settling in ether.
[0019] 5.0 g of PEG-PLA was heated to 120°C and vacuum dehydrated for 2 h. Then the temperature was lowered to 80°C, 1.3 g of HDI was added, and the mixture was reacted at 90°C for 2 h to generate a prepolymer.
[0020] The prepolymer was dispersed in 15.0 mL of water, heated to 50° C., and a stable prepolymer emulsion was formed by high-speed stirring. 0.4 g of BDO was added to the emulsion for chain extension reaction. After reacting for 4 hours, a polyurethane emulsion was obtained.
[0021] The prepared polyurethane emulsion is diluted to a solid content of 10%, poured into a mold, pre-frozen, and then freeze-dried under vacuum conditions to obtain a polyurethane porous material.
[0022] Example 2. Under nitrogen protection, 10.0 g of PEG with a molecular weight of 1000, 3.0 g of LA, and 2.5 mL of a 0.1 wt% stannous octoate toluene solution were heated to 140° C. for 12 h. After the reaction was completed, the amphiphilic copolymer PEG-PLA was obtained by dissolving in dichloromethane and settling in ether.
[0023] 5.0 g of PEG-PLA was heated to 120°C and vacuum dehydrated for 2 h. Then the temperature was lowered to 80°C, 1.3 g of HDI was added, and the mixture was reacted at 90°C for 2 h to generate a prepolymer.
[0024] The prepolymer was dispersed in 15.0 mL of water, heated to 50° C., and a stable prepolymer emulsion was formed by high-speed stirring. 0.4 g of BDO was added to the emulsion for chain extension reaction. After reacting for 4 hours, a polyurethane emulsion was obtained.
[0025] The prepared polyurethane emulsion is diluted to a solid content of 5%, poured into a mold, pre-frozen, and then freeze-dried under vacuum conditions to obtain a polyurethane porous material.
[0026] Example 3. Under nitrogen protection, 10.0 g of PEG with a molecular weight of 2000, 1.5 g of LA, and 2.5 mL of 0.1 wt% stannous octoate toluene solution were heated to 140° C. and reacted for 12 h. After the reaction was completed, the amphiphilic copolymer PEG-PLA was obtained by dissolving in dichloromethane and settling with ether.
[0027] 5.0 g of PEG-PLA was heated to 120°C and vacuum dehydrated for 2 h. Then the temperature was lowered to 80°C, 0.7 g of HDI was added, and the mixture was reacted at 90°C for 2 h to generate a prepolymer.
[0028] The prepolymer was dispersed in 15.0 mL of water, heated to 50° C., and a stable prepolymer emulsion was formed by high-speed stirring. 0.2 g of BDO was added to the emulsion for chain extension reaction. After reacting for 4 hours, a polyurethane emulsion was obtained.
[0029] The prepared polyurethane emulsion is diluted to a solid content of 10%, poured into a mold, pre-frozen, and then freeze-dried under vacuum conditions to obtain a polyurethane porous material.
[0030] Example 4. Under nitrogen protection, 10.0 g of PEG with a molecular weight of 1000, 2.0 g of PDO, and 2.5 mL of 0.1 wt% stannous octoate toluene solution were heated to 140° C. and reacted for 12 h. After the reaction was completed, the amphiphilic copolymer PEG-PPDO was obtained by dissolving in dichloromethane and settling with ether.
[0031] 5.0 g of PEG-PPDO was heated to 120°C and vacuum dehydrated for 2 h. Then the temperature was lowered to 80°C, 1.4 g of HDI was added, and the mixture was reacted at 90°C for 2 h to generate a prepolymer.
[0032] The prepolymer was dispersed in 15.0 mL of water, heated to 50° C., and a stable prepolymer emulsion was formed by high-speed stirring. 0.4 g of BDO was added to the emulsion for chain extension reaction. After reacting for 4 hours, a polyurethane emulsion was obtained.
[0033] The prepared polyurethane emulsion is diluted to a solid content of 10%, poured into a mold, pre-frozen, and then freeze-dried under vacuum conditions to obtain a polyurethane porous material.
[0034] Example 5. Under nitrogen protection, 10.0 g of PEG with a molecular weight of 1000, 1.4 g of LA, 1.2 g of GA, and 2.5 mL of 0.1 wt% stannous octoate toluene solution were heated to 140°C for reaction for 12 h. After the reaction was completed, the amphiphilic copolymer PEG-PLGA was obtained by dissolving in dichloromethane and settling with ether.
[0035] 5.0 g of PEG-PLGA was heated to 120°C and vacuum dehydrated for 2 h. Then the temperature was lowered to 80°C, 1.1 g of BDI was added, and the mixture was reacted at 90°C for 2 h to generate a prepolymer.
[0036] The prepolymer was dispersed in 15.0 mL of water, heated to 50° C., and a stable prepolymer emulsion was formed by high-speed stirring. 0.4 g of BDO was added to the emulsion for chain extension reaction. After reacting for 4 hours, a polyurethane emulsion was obtained.
[0037] The prepared polyurethane emulsion is diluted to a solid content of 10%, poured into a mold, pre-frozen, and then freeze-dried under vacuum conditions to obtain a polyurethane porous material.
[0038] Effect example. The various properties of the materials in the above examples 1 to 5 were tested: (1) Tensile properties: According to the national standard GB / T 6344-2008, the polyurethane porous materials prepared in Examples 1 to 5 were prepared into dumbbell-shaped samples, and the tensile properties were tested under a testing machine at a tensile speed of 50 mm / min.
[0039] (2) Water absorption rate: According to the national standard GB / T 1034-2008, the polyurethane porous materials prepared in Examples 1 to 5 were cut into samples with a size of about 20×20×2 mm, dried to a constant weight and recorded as m 1 Then, immerse it completely in deionized water for 1 hour, take it out and weigh it, record it as m 2 , then water absorption = (m 2 -m 1 ) / m 1 *100%.
[0040] (3) Degradation time: The polyurethane porous materials prepared in Examples 1 to 5 were cut into a size of 2×1×1 cm, placed in a sealed container filled with PBS solution, placed in a constant temperature shaker at 37±1°C, and the changes in the samples were observed and recorded. When the polyurethane porous material was broken, it was its degradation time.
[0041] The above test results are shown in Table 1.
[0042] Table 1
[0043] It can be proved that the tensile strength of the polyurethane porous material provided by the present invention is 0.35MPa~0.95MPa, which can better maintain the shape and structural integrity and is not easy to tear in actual use; the elongation at break is 129%~207%, indicating that the material has good flexibility. When used as hemostatic cotton, it can fit the wound well during contact and operation, and is not easy to cause secondary damage to the wound due to rigidity; the water absorption rate of hemostatic cotton is one of the key performance indicators. A higher water absorption rate can quickly absorb blood to achieve the purpose of hemostasis. The water absorption rate of each embodiment is 810%~1020%, and the water absorption rate is high, which can quickly and effectively absorb blood. As a medical material, after completing the hemostatic mission, the hemostatic cotton should be able to degrade within a reasonable time to avoid residual adverse effects on the human body. The degradation time is 28h~52h, which can ensure that the material remains stable during the hemostatic process and will not remain in the body for a long time. Therefore, in general, the polyurethane porous material provided by the present invention has the potential to become an excellent hemostatic cotton.
[0044] The material can also be used as a tissue engineering scaffold. The mechanical properties of the material can provide basic support, and the higher flexibility can better adapt to the physiological activities of the tissue and avoid damage to the surrounding tissue due to excessive rigidity. A higher water absorption rate indicates that the material has good hydrophilicity, and thus better biocompatibility, which is conducive to cell adhesion, growth and proliferation. The degradation time of the material is compatible with some tissues with faster repair speeds. In addition, it can also be used as a drug sustained-release carrier. The high water absorption rate means that the material has a larger porosity and a higher liquid holding capacity, which is conducive to drug loading, and more drugs can be loaded by adsorption or encapsulation. The drug release rate can be coordinated with the material degradation rate, and the slow and continuous release of the drug can be achieved to achieve a sustained-release effect. The material has a certain mechanical stability, which can ensure the integrity of the carrier structure during the drug sustained-release process to a certain extent.
[0045] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a polyurethane porous material, characterized in that: The steps include: S1. Under nitrogen protection, a toluene solution of polyethylene glycol, aliphatic cyclic ester monomer and stannous octoate is heated to 120°C to 140°C for reaction for 8h to 12h. After the reaction, the solution is dissolved in dichloromethane and then precipitated with ether to obtain an amphiphilic copolymer including polyethylene glycol segments and aliphatic polyester segments. S2, then heating the amphiphilic copolymer to 100° C. to 140° C., performing vacuum dehydration for 2 h, then cooling to 80° C. to 90° C., then adding diisocyanate, and reacting at 80° C. to 90° C. for 2 h to 3 h to generate a prepolymer; S3, dispersing the prepolymer in water, heating to 40°C to 50°C, stirring to form a stable prepolymer emulsion, adding a chain extender to the emulsion to carry out a chain extension reaction for 3h to 4h to obtain a polyurethane emulsion; S4. Dilute the prepared polyurethane emulsion to a solid content of 5% to 10%, pour it into a mold for pre-freezing, and then freeze-dry it under vacuum conditions to obtain a polyurethane porous material.
2. The method for preparing a polyurethane porous material according to claim 1, characterized in that: The aliphatic cyclic ester monomer in step S1 is at least one selected from lactide, glycolide, dioxanone, and caprolactone.
3. The method for preparing a polyurethane porous material according to claim 1, characterized in that: The molecular weight of the polyethylene glycol in step S1 is 500-5000; the mass ratio of the polyethylene glycol to the aliphatic cyclic ester monomer is 1:(0.1-2.5); the mass of the stannous octoate is 0.1‰-1‰ of the sum of the masses of the polyethylene glycol and the aliphatic cyclic ester monomer.
4. The method for preparing a polyurethane porous material according to claim 1, characterized in that: The diisocyanate in step S2 is any one of hexamethylene diisocyanate, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,4-diisocyanate butane, and 4,4'-dicyclohexylmethane diisocyanate.
5. The method for preparing a polyurethane porous material according to claim 1, characterized in that: The molar ratio of the amphiphilic copolymer to the diisocyanate in step S2 is 1:(2.0-3.0).
6. The method for preparing a polyurethane porous material according to claim 1, characterized in that: The chain extender in step S3 is a small molecule diol.
7. The method for preparing a polyurethane porous material according to claim 6, characterized in that: The chain extender is any one of 1,4-butanediol, hydroquinone dihydroxyethyl ether and ethylene glycol.
8. The method for preparing a polyurethane porous material according to claim 1, characterized in that: The molar ratio of the prepolymer to the small molecule diol in step S3 is 1:(1.0-2.0).
9. A polyurethane porous material, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. An application of the polyurethane porous material according to claim 9, characterized in that: It is used in the field of medical materials as a hemostatic material, tissue engineering scaffold or drug sustained-release carrier.
Citation Information
Patent Citations
Preparation method of biodegradable nasal hemostatic sponge
CN104031287A
Microcrystalline cellulose based eraser and preparation method thereof
CN117844060A
Hemostatic sponge capable of being integrally disintegrated as well as preparation method and application of hemostatic sponge
CN118576751A
Porous polyurethane object
CN1845942A
Production of porous sheet material
JP1990189345A